Delivery sheath tip invagination - An unusual cause of failure to retrieve duct occluder - Anunay Gupta; Saurabh Kumar Gupta; Sivasubramanian Ramakrishnan; Shyam S Kothari (Wolters Kluwer Medknow Publications, 2021)
Transcatheter closure of patent ductus arteriosus is the standard of care. Retrieval of a duct occluder device is generally easy until it is detached from the delivery cable. We report two instances of failed retrieval of the device due to sheath tip invagination. The report highlights the importance of prompt identification of the mechanism of unforeseen complications in managing it effectively.